Laser sintering and invalidating composite scan for improving tensile strength and accuracy of SLS parts. (August 2020) - Tong, Qiang; Xue, Kaihua; Wang, Tingli; Yao, Shan
Highlights: The laser sintering and invalidating composite (LSIC) scanning method is proposed. The large-spot laser scanning is used to sinter the inside of the sample efficiently，in order to realize high tensile strength of the parts. The small-spot laser scanning is used to invalidate the profile of the sample，in order to realize high accuracy of the parts. Composite scanning method solves the problem of the inter-limitation of tensile strength and accuracy of laser sintering forming. Abstract: The laser scanning method is one of the key factors in the process of selective laser sintering. Laser sintering and invalidating composite (LSIC) scanning method, which is composed of high tensile strength sintering scanning with large-spot and high accuracy invalidating scanning with small-spot, is able to improve the tensile strength, accuracy and fabrication efficiency of SLS parts. In this paper, the principle and implementation of this method were presented, and in order to prove the effectiveness of the method, the conventional scanning method was used to carry out the sintering forming experiments of the coated ceramics, and the relationship between the energy density, the tensile strength and accuracy of the parts was explored. Then based on the conclusion of this experiment, the composite scanning method is used for comparative sintering experiments. The results show that when the sintering process is carried out using the process parameters corresponding to the high tensile strength, a substantial amount of secondary sintered bodies is generated on the surface of the part and the accuracy is destroyed. The conventional scanning method cannot achieve high accuracy forming under this process condition. However, the composite scanning method can effectively eliminate the adverse influence of secondary sintering on accuracy, and achieve high tensile strength and high accuracy parts. Moreover, the method can also improve the fabrication efficiency. Therefore, this method is of great significance to realize high quality sand mould additive manufacturing and enrich the scanning method of SLS.